2012
DOI: 10.5630/jans.32.2_34
|View full text |Cite
|
Sign up to set email alerts
|

A Study on the Personal/Environmental Factors Related to the Actual Conditions of the Learning Needs of Clinical Nurses

Abstract: e purpose of this study was to clarify the personal/environmental factors related to clinical nurses learning needs and to discuss the concept of continuing education. e investigation was carried out with the nurses and the nurse administrators using a questionnaire that included personal and environmental factors and learning needs assessment tools. Valid responses were received from 719 of the subjects, and they were analyzed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…However, interactive workshops, rather than lectures and academic instruction, are the best method to promote changes in professional practice (Griscti & Jacono, 2006). Furthermore, it has been reported that, in addition to ensuring the self‐effort of nurses within hospitals, there is a need to establish networks with hospitals in neighboring regions because their desire (willingness) to learn is positively correlated with the presence of training facilities (Takahashi, Kiyomura, Kajiwara, & Itoh, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…However, interactive workshops, rather than lectures and academic instruction, are the best method to promote changes in professional practice (Griscti & Jacono, 2006). Furthermore, it has been reported that, in addition to ensuring the self‐effort of nurses within hospitals, there is a need to establish networks with hospitals in neighboring regions because their desire (willingness) to learn is positively correlated with the presence of training facilities (Takahashi, Kiyomura, Kajiwara, & Itoh, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The principal factors found to be associated with ability to develop staff were "gathering and using information" and "supportiveness of the work environment." A previous study by Takahashi, Kiyomura, Kajiwara, and Itou [22] suggested that the learning needs of clinical nurses (including managers) may be influenced by their educational backgrounds and the type of hospital they work in. Since learning needs and training are closely related concepts, we assumed that the explanatory factors associated with them should be similar.…”
Section: Discussionmentioning
confidence: 99%